A novel E-DTDOA based one-way ranging using UWB-IR with unsynchronized anchors - Vashistha, Ankush (2022)
In this article, a novel analytical equation is proposed to determine the equivalent time of arrival (E-TOA) for achieving sub-ns resolution, with much reduced analog-to-digital converter sampling frequency (in the order of 2-3 MHz). The timing information is extracted from high resolution channel impulse response, which is obtained using an equivalent time sampling (ETS) technique. The proposed E-TOA equation is different from the conventional real-time sampling equation due to the presence of an additional transmitter clock drift, and thus sensitive to both the transmitter and receiver clock drift variations. The validation of the E-TOA equation is carried out numerically using simulations along with experimental validation. The effect of timing uncertainties relating to the transmitter clock start time and the receiver clock offset is analyzed with variations in the transmitter and receiver clock drifts. With E-TOA measurements, an equivalent differential time difference of arrival based one-way ranging scheme for unsynchronized anchors is further proposed. It is thus demonstrated, using in house designed sensor nodes, that high ranging accuracy, in the order of few centimeters, can be achieved by utilizing the proposed analytical E-TOA technique, even with low sampling rate.